Mulberry and the summer show - Golden, Che (Oxford, [U.K.] Oxford University Press, 2013)
"Mulberry is the bad-tempered pony no one wants to ride. So when shy girl Sam enters them both in the Summer Show, everyone thinks she's crazy. But Sam has a secret weapon - she can talk to horses. The only problem is, Mulberry isn't keen on listening and time is running out. Will they learn to work together? Includes free pony stickers!"
"The Meadow Vale ponies."--Cover.
Keywords: Children's stories